Laparoscopic sleeve gastrectomy in the South Pacific. Retrospective evaluation of 510 patients in a single institution. (June 2016) - Lemaître, Frédéric; Léger, Philippe; Nedelcu, Marius; Nocca, David
Abstract: Introduction: The South Pacific has a high prevalence of obesity and super-obesity. We reviewed our experience with laparoscopic sleeve gastrectomy (LSG) to evaluate its efficacy and safety. Methods: A retrospective review of a prospectively collected database of LSGs carried out by one surgeon in one center. The percentage of excess weight loss and the rate of resolution or improvement of comorbidities reflected efficacy, and major complications or mortalities reflected safety. Results: From January 2008 to February 2013, we performed 510 surgeries and included 494 consecutive patients (367 females) (45.5 ± 11.2 years) in our study. LSG was the primary procedure in 384 patients, 6 patients had redo bariatric surgery after failure of initial LSG, 57 patients had a history of gastric banding with insufficient weight loss or band-related complications, and 46 super-obese patients had an intragastric balloon placed before LSG. Average starting body mass index was 47.8 kg m −2 . Mean percent excess weight loss was 64.3% at 1 year; 67.3% at 2 years and 66.4% at 3 years. The percentages of resolved comorbidities were as follows: hypertension: 48.3%, type 2 diabetes mellitus: 72.5%, dyslipidemia: 61.0%, and obstructive sleep apnea: 77.8%. The mortality rate was 1/494. The postoperative morbidity included gastric fistula in 3.0%, hemorrhaging in 2.4%, and postoperative gastroesophageal reflux in 9.4%. Conclusions: In the South Pacific, LSG is a safe and effective means of treating morbid obesity with sustained weight loss and resolution of comorbid medical conditions. Highlights: Excess weight loss diminished among patients undergoing sleeve gastrectomy. Sleeve gastrectomy is effective to reduce cardiometabolic parameters. Sleeve gastrectomy is a safe means of treating morbid obesity.